Fungal eicosanoid biosynthesis Influences the virulence of Candida Parapsilosis - Chakraborty Tanmoy (2019)
The increased incidence and high mortality rate of fungal infections in immunocompromised patients have become a serious concern in hospitals since the early 1990s. Among different pathogenic fungi, Candida spp. remain the most prevalent cause of invasive fungal infections, exceeding invasive aspergillosis and mucormycosis. Although, C. albicans is still the most common cause of invasive candidiasis, bloodstream infections caused by non-albicans Candida species such as C. glabrata, C. krusei, C. auris, C. parapsilosis and C. tropicalis, altogether have risen to account for approximately one-half of all candidemia cases. C. parapsilosis is ubiquitous in nature and commonly found on the surface of the human skin as a commensal. It is also frequently isolated from the gastrointestinal tract. It is the leading cause of invasive fungal infections in premature infants. Among non-albicans Candida spp., the incidence of C. parapsilosis is increasing in this particular patient group and in some hospitals, it even outnumbers C. albicans infections. Risk factors that are associated with C. parapsilosis driven neonatal candidiasis includes low birth weight (<1500 g), prematurity, prior colonization, the use of parenteral nutrition, intravascular catheters and prolonged treatment with antibiotics or steroids. This species is especially capable of forming biofilm on abiotic surfaces such as catheters, prostheses or other implanted devices, further increasing the chances for invasive infections. 2 It has been shown before that C. parapsilosis can produce immunomodulatory prostaglandin molecules from exogenous arachidonic acid. But the pathways regarding the prostaglandin production is still not known. So, the purpose of this study was to identify genes in C. parapsilosis associated with the production of immunomodulatory eicosanoid molecules and decipher their role in host pathogen interactions. Furthermore, we also investigated the role of a homologue of a multicopper oxidase in pseudohyphae and biofilm formation in this medically relevant fungus.